Variations in Duration of Clinical Follow-up After Spinal Fusion for Adolescent Idiopathic Scoliosis: A Survey of POSNA and SRS Membership: Original Research - Johnson, Taylor R.; A. Segovia, Nicole; Bryson, Xochitl; Imrie, Meghan; Vorhies, John (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Background: There are currently no evidence-based guidelines addressing the duration of follow-up after spinal fusion. Despite the safety and efficacy of posterior spinal fusion (PSF) for Adolescent Idiopathic Scoliosis (AIS), long-term complications exist, including infection, pseudoarthrosis, adjacent segment disease, deformity progression, persistent pain, and junctional deformities. The objective of this study was to describe practice variation existing among surgeons regarding duration of follow-up after surgical treatment of AIS. Methods: An anonymous online survey was created and subsequently distributed to members of POSNA and SRS to assess practice demographics and surgeon opinions surrounding long-term surveillance following surgery for AIS. Only surgeons who treated at least 5 operative AIS cases within the past year were included. Descriptive statistics and comparative sub-analyses are presented. Results: Forty-nine participants met inclusion criteria. Respondents were mainly Pediatric Orthopaedic Surgeons (92%) in practice for 21-50 years (49%) who performed approximately 21-50 operative AIS cases per year (49%). 48% of providers had an age limit in their practice and 52% regularly followed operative AIS patients over 18 years of age. 62% of surgeons followed operative AIS patients for 2-5 years post-operatively whereas only 4% followed for more than 10 years. The most cited factors impacting follow-up recommendations were junctional deformities, adjacent segment disease, and symptomatic implants. There were no significant associations between years in practice, operative volume and, for long-term follow-up after routine operative AIS cases. Conclusions: Significant variability in long-term follow-up after PSF for AIS exists. Although most patients are clinically followed for 2 years after surgery, only a small percentage of providers follow AIS patients for more than 10 years post-operatively. Numerous AIS revisions occur more than 5 years after the index surgery. Further investigations to determine the benefits of long-term surveillance following PSF for AIS should be conducted.